Hubungan Obesitas Dengan Terjadinya Gangguan Pendengaran Sensorineural - Rahmi Sibagariang; Muhammad Edy Syahputra Nasution; Siti Masliana Siregar; Isra Thristy (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Obesity is an increase in total body fat, that is if found to be overweight > 20% in men and 25% in women due to fat. Increased obesity cannot beseparated from lifestyle, such as decreased physical activity. One complication that can be caused by obesity is hearing loss, especiallysensorineural hearing loss caused by microangiopathic abnormalities, especially in the inner ear. But the relationship of events between obesity withhearing loss is still often a debate, because there is no definite consensus. The purpose of this research determine the relationship of obesity with sensorineural hearing loss. This research is an analytic study by obtaining cross-sectional study, with data obtained from the assessment of bodyweight and height to see the status of the mass index, physical examination of the ear, and audiometric examination. Data analysis techniques using the chi square test statistics. Research result obtained relationship between obesity with sensorineural hearing loss as much as 49.09% and the highest degree of hearing loss is mild degrees as much as 27.07%. Research conclusions there is a significant relationship between obesity with sensorineural hearing loss. Keyword: Hearing Loss, Obesity, Obesity with Hearing Loss, Pure Tone Audiometry, Sensorineural Hearing Loss,